N-Containing Graphene Preparation Using Melamine as a Nitrogen Source - Ivanova, N.M.; Muldakhmetov, Z.M.; Vissurkhanova, Ya.A.; Soboleva, Ye.A.; Borsynbayev, A.S. (Karagandy University of the name of academician E.A. Buketov, 2025)
N-doped graphene is not only a promising metal-free catalyst, but also a convenient carrier of metal nanoparticles for the creation of effective catalysts. Graphitic carbon nitride (g-C3N4) is used more often in photocatalytic processes and less often as electrocatalysts. This paper describes the preparation of N-containing carbon composites consisting of reduced graphene oxide (rGO) and g-C3N4 for the further creation of metal-carbon catalytic systems. These composites were prepared by the heat treating dry mixtures of graphene oxide (GO) and melamine (MA) in the temperature range of 450–550 °C in air. Oxygen-containing groups were identified in the graphene oxide samples synthesized by the modified Hummers method and in its reduced form.The thermogravimetric analysis method was used to determine the ranges of relative thermal stability of the GO + MA mixtures, which were found to be almost identical for the studied compositions with different component ratios. The structure of the graphene oxide and its composites with MA after heat treatment was studied by scanning electron spectroscopy, X-ray diffraction analysis, FTIR spectroscopy and elemental analysis. The effect of the ratio of the initial components on the formation of the heat treatment products was determined. It was shown that to obtain the rGO+g-C3N4 composites with a high content of carbon nitride, the ratio of the initial reagents should be taken equal to 1:2, and the heat treatment should be carried out at 550 °C.
Keywords: graphene oxide; oxygen-containing functional groups; melamine; “dry” preparation method; heat treatment; reduced graphene oxide; graphitic carbon nitride; elemental content